Sensitivity of resolved and parametrized surface drag to changes in resolution and parametrization. (7th June 2016) - van Niekerk, Annelize; Shepherd, Theodore G.; Vosper, Simon B.; Webster, Stuart
Abstract : The relative contributions of resolved and parametrized surface drag towards balancing the atmospheric angular momentum flux convergence (AMFC) and their sensitivity to horizontal resolution and parametrization are investigated in an atmospheric model. This sensitivity can be difficult to elucidate in free‐running climate models, in which the AMFC varies with changing climatologies and, as a result, the relative contributions of surface terms balancing the AMFC also vary. While the sensitivity question has previously been addressed using short‐range forecasts, we demonstrate that a nudging framework is an effective method for constraining the AMFC. The Met Office Unified Model is integrated at three horizontal resolutions ranging from 130 ( N 96) to 25 km ( N 512), while relaxing the model's wind and temperature fields towards the ERA‐Interim reanalysis within the altitude regions of maximum AMFC. This method is validated against short‐range forecasts and good agreement is found. These experiments are then used to assess the fidelity of the exchange between parametrized and resolved orographic torques with changes in horizontal resolution. Although the parametrized orographic torque reduces substantially with increasing horizontal resolution, there is little change in resolved orographic torque over 20–50°N. The tendencies produced by the nudging routine indicate that the additional drag at lower horizontal resolution is excessive. When parametrized orographic blocking is removed at the coarsest of these resolutions, there is a lack of compensation, and even compensation of the opposite sense, by the boundary layer and resolved torques, which is particularly pronounced over 20–50°N. This study demonstrates that there is strong sensitivity in the behaviour of the resolved and parametrized surface drag over this region.